DAUR NAADI AL-MUNAZHARAH FII TANMIYATI AL-KIFAYAH ASY-SYAFAWIYAH WA RUUH AL-MUNAAFASAH: دور نادي المناظرة باللغة العربية في بناء الكفاءة اللغوية الشفوية وتنمية روح المنافسة - Mhd Firdaus Lubis; Mohammed Abdulaziz Mohammed AhmedEltigani; Hajer Abdallah Albshkar (Lahjah Arabiyah : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
This study aims to examine the role of the Arabic debate club in developing Arabic speaking skills and enhancing positive competitive spirit among students at Al-Tibyan Islamic Boarding School, a newly established institution with an age not exceeding six years. The study is based on the problem of the persistent weakness in Arabic speaking skills due to the dominance of theoretical teaching approaches and the limited opportunities for interactive oral practice, as well as the scarcity of studies addressing debate as an institutional educational framework within Islamic boarding schools. The study employs a qualitative approach through observation, interviews, and document analysis related to debate activities over the past three years. The findings reveal that debate activities significantly contribute to improving speaking fluency, grammatical accuracy, argumentative skills, and students’ self-confidence. They also enhance learning motivation, strengthen positive competition, and prepare students for participation in various local, national, and international competitions. Despite challenges such as the limited number of Arabic debate competitions in Sumatra, the study confirms that Arabic debate represents an effective instructional strategy for developing oral proficiency in Islamic educational environments.